2001
DOI: 10.1515/crll.2001.035
|View full text |Cite
|
Sign up to set email alerts
|

Isospectral manifolds with different local geometries

Abstract: Abstract. We construct several new classes of isospectral manifolds with different local geometries. After reviewing a theorem by Carolyn Gordon on isospectral torus bundles and presenting certain useful specialized versions (Chapter 1) we apply these tools to construct the first examples of isospectral four-dimensional manifolds which are not locally isometric (Chapter 2). Moreover, we construct the first examples of isospectral left invariant metrics on compact Lie groups (Chapter 3). Thereby we also obtain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 44 publications
1
37
0
Order By: Relevance
“…Recently, we have learned that Schueth has also obtained examples of isospectral homogeneous spaces [Sch2]. In fact, she produces a continuous family of pairwise isospectral left-invariant metrics on a simply-connected Lie group.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have learned that Schueth has also obtained examples of isospectral homogeneous spaces [Sch2]. In fact, she produces a continuous family of pairwise isospectral left-invariant metrics on a simply-connected Lie group.…”
Section: Introductionmentioning
confidence: 99%
“…We compare the spectrum of each such symmetric space with the spectra of arbitrary left-invariant metrics on the Lie group. As a departure point we note that the second author showed that there are no non-trivial continuous isospectral deformations of a biinvariant metric within the class of left-invariant metrics on a compact Lie group [10]. This prompts one to ask whether a bi-invariant metric on a compact Lie group G is spectrally isolated within the class of left-invariant metrics.…”
Section: Annales De L'institut Fouriermentioning
confidence: 98%
“…The proof of Theorem 1.1 uses the Riemannian submersion method (see, e.g., [10], [9], [13], [30], [31], [32]). The present paper generalizes previous results of Gordon and the first author [11], who constructed continuous families of compactly supported perturbations of the Euclidean metric on R n with the same scattering phase.…”
Section: Remark 13 (I)mentioning
confidence: 99%